2008
DOI: 10.1007/s12010-008-8199-y
|View full text |Cite
|
Sign up to set email alerts
|

New Method Showing the Influence of Matrix Components in Leuconostoc mesenteroides Biofilm Formation

Abstract: Studying biofilm formation and influence of the matrix composition was heavy because only old and long methods were employed up to now: confocal microscopy, fluorescent chemical markers, and/or dying techniques. In this context, an innovative tool, the BioFilm Ring Test, was here employed to explore the role of exopolysaccharides, proteins, and nucleic acids in the formation of biofilm by Leuconostoc mesenteroides. The principle is to add magnetic particles in the culture medium. When a biofilm is formed, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 14 publications
1
13
1
Order By: Relevance
“…The Biofilm Ring Test was further developed to test the sensitivity to antibiotics of clinical isolates in biofilm as "the antibiofilmogram", which provides complementary and sometimes more relevant information compared to a classical antibiogram. The Biofilm Ring Test has also been extended to study the contribution of different molecular determinants to the mechanisms of biofilm formation by different bacterial species (Badel et al, 2008(Badel et al, , 2011. Like the microtiter plate, the Biofilm Ring Test is sensitive to sedimentation due to gravity.…”
Section: Microtiter Platesmentioning
confidence: 99%
“…The Biofilm Ring Test was further developed to test the sensitivity to antibiotics of clinical isolates in biofilm as "the antibiofilmogram", which provides complementary and sometimes more relevant information compared to a classical antibiogram. The Biofilm Ring Test has also been extended to study the contribution of different molecular determinants to the mechanisms of biofilm formation by different bacterial species (Badel et al, 2008(Badel et al, , 2011. Like the microtiter plate, the Biofilm Ring Test is sensitive to sedimentation due to gravity.…”
Section: Microtiter Platesmentioning
confidence: 99%
“…This is generally used to study the kinetics of biofilm formation of Listeria monocytogenes, E. coli, Staphylococcus carnosus and Staphylococcus xylosus, 143 to measure the biofilm matrix mechanisms on Leuconostoc mesenteroides biofilm formation. 144 It can also be used to assess the antibiotics' effects on P. aeruginosa biofilms, 145 to relate the formation of biofilm among Campylobacter coli and Campylobacter jejuni. 146 Flow displacement method.…”
Section: Treatment Of Medical Implant-associated Infections With Nanomentioning
confidence: 99%
“…Fogler (1999, 2000) concluded that dextran was important for biofilm formation of one strain of L. mesenteroides in porous medium. Badel et al (2008) found that dextran, proteins, and nucleic acids were all implied in biofilm formation by another strain of L. mesenteroides. On the other hand, some studies suggest that polysaccharides may not always be essential for biofilm formation (Jahn and Nielsen 1998;Wozniak et al 2003).…”
Section: Introductionmentioning
confidence: 96%